A Pilot Study of Body Composition and Bone Mineral Density in Healthy Men From Argentina - Seijo, Mariana (2007)
A precise assessment of bone mineral density (BMD) and body composition can be performed using dual-energy X-ray absorptiometry (DXA). Values of body composition for males would be useful to evaluate the occurrence of alterations in body composition in a number of diseases. The objectives of this study were to establish BMD and body composition values in healthy men and to analyze age-related changes. BMD and body composition of total body and subareas were determined in 116 healthy men (aged 20e79 yr) using DXA. Comparison between 20e29- and 70e79-yr-old men showed that older subjects were shorter ( p!0.03), and had a higher body mass index ( p!0.01). Fat mass increased (þ46.7%; p!0.001) especially in the trunk. Lean mass (LM) decreased (9.4%; p!0.05) mainly in the arms and legs. Bone mineral content (BMC) and BMD decreased (15.3% [p!0.001], 6.3% [p!0.05], respectively). Correlation was observed between BMC and LM (r50.7, p!0.01). Values of BMD and body composition in healthy men were obtained. A relation was observed between bone mass and body composition, suggesting that the age-related decrease in LM may be associated to bone mass loss. Further studies should be conducted to elucidate the role of body composition in the occurrence of osteoporosis in men.